The Problems of Proving Electronic Evidence - Setyawan, Vincentius (Fundamental: Jurnal Ilmiah Hukum, 2022)
The purpose of writing this article is to present the results of research on the problems in the existence of electronic evidence in proving civil cases, criminal cases, and state administrative cases, as well as finding solutions to these problems. This article was written using a normative legal research method with a statutory approach and a conceptual approach. The results of this study determine that there is a need for synchronization of rules regarding electronic evidence as regulated in Law Number 11 of 2008 concerning Electronic Information and Transactions as amended by Law Number 19 of 2016, and rules of procedural law, both legal criminal procedure, civil procedural law and state administrative procedural law. Keywords: Electronic Evidence, Synchronization, Procedure Law